(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Education in India has been a contested terrain. The modern Indian state has made education mandatory as a policy measure. However, systemic constraints still prevail based on economy, language, region, caste and gender. The education sector is not a level-playing field, dotted with government schools with limited resources and specialized schools reserved for a chosen few. Purpose of this research is to find out how the dominance of one language in the education-system affects the students acquiring knowledge and thought process and their relational aspects with others? Does it only affect the material elements of knowledge-power or the psychological and emotional issues of everyday student’s life and their lived experience? Because, Student from the regional background are discriminated upon as against the English medium students their sufferings become multitude and comprises as socially, economically, emotionally, psychologically and intellectually.